Production system of indigenous goat population reared in pastoral and agro-pastoral districts of South Omo, Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2023)
The study was carried out to document the production system of indigenous Woyto-Guji goats and the major limitations to goat production reared in two districts (Nyangatom and Maale) of South Omo, Ethiopia. Stepwise purposive followed by a random sampling method was used to select respondents. Based on the result, the households in Nyangatom district preferred to rear cattle, goats and sheep and less number of poultry when compared to those residing in the Maale district. The purpose of keeping goats in the district was primarily for tangible and intangible benefits. They are raised for their milk, meat, and blood as a source of wealth creation and insurance against emergencies. The results also indicated that the respondents in Maale district provide feed supplements. Communal grazing is prevalent in Nyangatom district, while in the Maale district, they interchangeably used both communal and private grazing lands; this all depended on the carrying capacity of the grazing land. Natural grazing and browsing the bush was the common form of feeding in both the study areas, while crop residues too were provided in Maale district. The sources of water varied across the study areas, the respondents in Nyangatom district relied solely on river Omo, ‘Omo shesh’ and ‘kure shesh’. While the flocks in Maale district were provided with water in the nearby streams besides the river water. The frequency of delivering water in the districts showed that every alternate day at Nyangatom and daily in the Maale district. The major limitation towards goat production in Nyangatom district was the unavailability of feed mainly in the dry season, followed by incidences of diseases; while some also indicated the problems associated with erratic and decrease in rainfall, thefts of the livestock were the identified problems. In Maale district, disease prevalence was major problem in the area as well as feed shortages followed by shrinkage of grazing lands, predators and lack of herders to take the animals for grazing. The current result on the production and farming system of goats and the major problems associated with goat production in the district helps to design different intervention options for the district.Int. J. Agril. Res. Innov. Tech. 13(1): 51-59, June 2023